2016
DOI: 10.1186/s12881-016-0331-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations of recurrent miscarriages with chromosomal abnormalities, thrombophilia allelic polymorphisms and/or consanguinity in Saudi Arabia

Abstract: BackgroundRecurrent pregnancy loss (RPL) or recurrent spontaneous abortion is an obstetric complication that affects couples at reproductive age. Previous reports documented a clear relationship between parents with chromosomal abnormalities and both recurrent miscarriages and infertility. However, limited data is available from the Arabian Peninsula which is known by higher rates of consanguineous marriages. The main goal of this study was to determine the prevalence of chromosomal abnormalities and thromboph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 79 publications
(82 reference statements)
2
31
2
2
Order By: Relevance
“…Recurrent early pregnancy loss (REPL), defined as two or more consecutive pregnancy losses at <10 weeks of gestation, affects 5% of couples aimed at childbirth [1]. While fetal chromosomal abnormalities represent the major factor behind sporadic miscarriages, they account for a smaller fraction of miscarriage events in REPL couples [2,3]. Currently available diagnostic procedures allow to identify clinical conditions increasing their risk to pregnancy failure and to offer appropriate management options only in 50% of REPL couples [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent early pregnancy loss (REPL), defined as two or more consecutive pregnancy losses at <10 weeks of gestation, affects 5% of couples aimed at childbirth [1]. While fetal chromosomal abnormalities represent the major factor behind sporadic miscarriages, they account for a smaller fraction of miscarriage events in REPL couples [2,3]. Currently available diagnostic procedures allow to identify clinical conditions increasing their risk to pregnancy failure and to offer appropriate management options only in 50% of REPL couples [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, a study showed that the frequencies of FVL and prothrombin mutations among recurrent miscarriages patients were relatively high compared to general incidence supporting the hypothesis of considering them as RPL genetic factors [25].…”
Section: Discussionmentioning
confidence: 95%
“…In terms of other serious complications, pulmonary embolism has been reported in a 19-year-old patient with type I antithrombin deficiency and a PT 20210 mutation [ Table 1 ],[ 10 ] and recurrent pregnancy loss was observed in Saudi females with allelic polymorphisms in FVL and PT 20210 genes. [ 19 ] Similarly, in an early study from Germany, genomic mutations of PT and FVL were reported in 9.3% of women, and this increased the risk of VTE during pregnancy and puerperium. [ 20 ] In children, although the risk of stroke has been independently associated with the homozygous MTHFR mutations alone, recurrent stroke as well as a combination of three inherited mutations (PT G20210A, MTHFR and plasminogen activator inhibitor-1) has been recently reported in a Saudi child.…”
Section: Discussionmentioning
confidence: 99%